2006
DOI: 10.1111/j.1528-1167.2006.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment Is Not Equal in Patients with Epileptic and Psychogenic Nonepileptic Seizures

Abstract: Summary:Purpose: Patients with psychogenic nonepileptic seizures (PNES) and those with epileptic seizures (ES) purportedly have roughly equal neurocognitive deficits. However, recent findings suggest that patients with somatoform disorders exhibit more variable effort on neurocognitive testing than do controls. We reexamined neurocognitive function in patients with ESs and PNES by using symptom validity testing to control for variability in effort.Methods: Patients referred for video-EEG monitoring were admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 29 publications
(42 reference statements)
5
60
2
2
Order By: Relevance
“…There has been some literature suggesting that poor performance on cognitive tests in this group might be explained by reduced effort (61). However, this explanation does not adequately explain the specificity of the deficits to recognition accuracy, as it might be expected that reduced effort would also lead to poor performance for intensity judgements and/or on the standardised cognitive tests administered here.…”
Section: Discussionmentioning
confidence: 62%
“…There has been some literature suggesting that poor performance on cognitive tests in this group might be explained by reduced effort (61). However, this explanation does not adequately explain the specificity of the deficits to recognition accuracy, as it might be expected that reduced effort would also lead to poor performance for intensity judgements and/or on the standardised cognitive tests administered here.…”
Section: Discussionmentioning
confidence: 62%
“…122 Binder et al 123 compared individuals with intractable seizures, showing that patients with PNES (N=34) had fewer correct on the Portland Digit Recognition Test (PDRT). Drane et al 124 compared individuals with PNES (N=43) and ES (N=70) using the WMT and a battery of cognitive tests, which provided the Dodrill Discrimination Index (DDI) or percentage of scores falling in the abnormal range. Although both groups had the same DDI score (50.3 versus 52.6), patients with PNES who failed the WMT performed much worse on the DDI than those who did not fail the WMT.…”
Section: Cognitionmentioning
confidence: 99%
“…A Dutch study of nearly 2000 healthy subjects found that as many as 29% of people aged [25][26][27][28][29][30][31][32][33][34][35] considered themselves forgetful, rising to 34% (40-50 years), 41% (55-65) years and 52% between 70-85 years [3]. High proportions (47-60%) of these respondents said they were worried to some extent about their forgetfulness Complaints of forgetfulness were correlated with depression and poor subjective health.…”
Section: Memory Symptoms In the General Populationmentioning
confidence: 99%